2003
DOI: 10.1039/b211887d
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic optical resolution via acylation–hydrolysis on a solid support

Abstract: By taking advantage of the reversibility of the thermolysin-catalysed amide synthesis-hydrolysis reaction on a solid support, both L,L and L,D diastereoisomers of dipeptides and L-amino acids are accessible in good yields starting from enantiomeric mixtures of amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…[19] Flitsch and co-workers showed the process was highly selective for the terminal l enantiomer for both amino acids tested, phenylalanine and norleucine, generatingh ighly enriched free amino acids (99 % ee). [19] The l,d-dipeptide was isolated cleanly as one diastereomer after separation from the reactionm ixture by filtration and cleavage from the polymer. The reverser eaction is also highly selective, with the sole incorporation of an l amino acid from ar acemic mixture onto aP EGA polymer derivatized with l-phenylalanine.…”
Section: Resolution Of Carboxylic Acid Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Flitsch and co-workers showed the process was highly selective for the terminal l enantiomer for both amino acids tested, phenylalanine and norleucine, generatingh ighly enriched free amino acids (99 % ee). [19] The l,d-dipeptide was isolated cleanly as one diastereomer after separation from the reactionm ixture by filtration and cleavage from the polymer. The reverser eaction is also highly selective, with the sole incorporation of an l amino acid from ar acemic mixture onto aP EGA polymer derivatized with l-phenylalanine.…”
Section: Resolution Of Carboxylic Acid Derivativesmentioning
confidence: 99%
“…The protease thermolysin is a robust biocatalyst that can both synthesize and hydrolyze peptide bonds . This hydrolysis reaction was used in the kinetic resolution of amino acids by selective removal of one enantiomer of an amino acid from an equal mixture of l,l ‐ and l,d ‐dipeptide diastereomers bound to a poly‐(acrylamide)‐ethylene glycol (PEGA) support (Scheme ) . Flitsch and co‐workers showed the process was highly selective for the terminal l enantiomer for both amino acids tested, phenylalanine and norleucine, generating highly enriched free amino acids (99 % ee ) .…”
Section: Asymmetric Removal From Polymermentioning
confidence: 99%
“…For example proteases are used to couple protected amino acids, but rely on high enzyme loadings and displacing unfavourable equilibria with either excess reagents, solubility effects or organic solvents, Scheme 1c. 11,[16][17][18][19][20][21][22] Surprisingly, the pioneering work done in the 1950-60s by Bartlett and Hirschmann describing the coupling of N-carboxyanhydride (NCA or Leuch's anhydride) to amino acids has not been widely adopted, despite it being productive, cost effective and green, Scheme 2. [23][24][25][26][27] Scheme 2.…”
Section: Introductionmentioning
confidence: 99%
“…Proteases catalyze the thermodynamically controlled synthesis in aqueous buffer while avoiding racemization and the needs for side chain protection of amino acids [12]. …”
mentioning
confidence: 99%
“…Moreover, it was observed that the formation of the peptide bond is thermodynamically favored when performed on SP—as compared to the process carried out in solution—even though the heterogeneous reaction takes place in a bulk aqueous environment [12]. …”
mentioning
confidence: 99%